(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The theoretical foundations of artistic analysis in the fine arts serve as a critical framework for understanding, interpreting, and evaluating artworks. This study explores the philosophical, historical, and aesthetic principles that underpin the analysis of visual art forms. It examines key methodologies derived from formalism, iconology, semiotics, and hermeneutics, as well as contemporary approaches influenced by psychology, sociology, and cultural studies. By integrating these diverse theoretical perspectives, the research aims to provide a comprehensive understanding of how meaning, style, symbolism, and context contribute to the depth and significance of artworks. The study emphasizes the importance of critical observation, contextual awareness, and interdisciplinary insight in fostering a deeper appreciation of visual expression. Ultimately, this research contributes to the development of a systematic and reflective approach to artistic analysis in both academic and creative fields.